2002
DOI: 10.1002/jrs.922
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on 1,5‐diaminoanthraquinone by laser excitation

Abstract: Optical absorption and fluorescence emission spectra of 1,5-diaminoanthraquinone (1,5-DAAQ) in different solvents and the surface-enhanced Raman scattering (SERS) spectrum of 1,5-DAAQ in silver sol were investigated. Optical absorption and fluorescence emission studies revealed that the internal and external hydrogen bonds and reorientation of the solvent molecule around the excited state fluorophore are responsible for the observed bathochromic shift and the non-radiative decay process in polar solvents. SERS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The assignments of SERS spectra of a-PMMA film dip-coated on Ag substrate are listed in Table 1. [25][26][27] It can be found that the orientation of PMMA chains of a-PMMA film dip-coated on Ag substrate is different from that of the normal PMMA film due to the interfacial interaction between polymer and Ag metal. To get the qualitative information about the molecular orientation, we avoid the disturbance of the band distortions by comparing with the relative intensity of band in the same spectra.…”
Section: Results and Discussion A-pmma Nss Analysismentioning
confidence: 99%
“…The assignments of SERS spectra of a-PMMA film dip-coated on Ag substrate are listed in Table 1. [25][26][27] It can be found that the orientation of PMMA chains of a-PMMA film dip-coated on Ag substrate is different from that of the normal PMMA film due to the interfacial interaction between polymer and Ag metal. To get the qualitative information about the molecular orientation, we avoid the disturbance of the band distortions by comparing with the relative intensity of band in the same spectra.…”
Section: Results and Discussion A-pmma Nss Analysismentioning
confidence: 99%
“…The shape, position, and intensity of the excitation and emission spectra of the PDAA nanoparticles differ significantly from those of the DAA monomer. [29] In particular, the excitation and emission intensities of the PDAA nanoparticles in NMP, due to fluorescence reinforcement by polyaniline-like p-conjugated chains, are almost six times stronger than those of DAA monomer at the same concentration in NMP. This phenomenon reflects the fact that the molecular structure of PDAA nanoparticles is quite different from that of the DAA monomer.…”
Section: Bulk Electrical Conductivitymentioning
confidence: 99%
“…The observed quantum yield reveals that the intermolecular hydrogen bond does not participate appreciably in the radiationless decay as in the case of anthraquinone derivatives. 15,19 In the case of polar aprotic solvents the observed quantum yield suggests that the dipole-dipole interaction in the excited state participates in the radiationless decay. The lower quantum yield in apolar solvents shows that dipole-induced dipole interaction increases the radiationless decay rate.…”
Section: 3-bis(chloromethyl)-14-naphthoquinone (2)mentioning
confidence: 99%